Normal ranges of non-invasive left ventricular myocardial work indices in healthy young people - Luo, Xiuxia; Ge, Quanrong; Su, Jin; Zhou, Ning; Li, Ping; Xiao, Xu; Chen, Yan; Wang, Dong; Ma, Yujing; Ma, Li; Zhu, Yongsheng (Frontiers in Pediatrics, 2022)
Objectives: Echocardiographic global myocardial work (GMW) indices recently emerged to non-invasively evaluate left ventricular (LV) myocardial performance with less load-dependence than LV ejection fraction (LVEF) or global longitudinal strain (GLS). Yet, few data exist on the descriptions of LV GMW indices in young people. We therefore aimed to provide normal reference values of LV GMW in a healthy young cohort, and simultaneously to investigate factors associated with non-invasive GMW indices. Methods: A total of 155 healthy young people (age 10-24years, 59% male) underwent transthoracic echocardiography were recruited and further stratified for age groups and divided by gender. Two-dimensional speckle-tracking imaging (2D-STI) were performed to determine LV GLS, peak strain dispersion (PSD) and GMW indices, which includes global work index (GWI), global constructive work (GCW), global wasted work (GWW), and global work efficiency (GWE). LV peak systolic pressure was assumed to be equal to the systolic brachial artery cuff blood pressure. Results: Age and gender specific normal ranges for LV GMW indices were presented. On multivariable analysis, GWI and GCW correlated more closely with systolic blood pressure (SBP) than LV GLS, while both GWW and GWE independently correlated with PSD (P < 0.05 for all). There were no associations between any of the GMW indices with age, sex, body mass index, heart rate, left ventricular mass index as well as LV sizes or LVEF. Of noted, LV GMW indices had good intra-observer and inter-observer reproducibility. Conclusion: We reported echocardiographic reference ranges for non-invasive LV GMW indices in a large group of healthy young subjects, which are reproducible and reliable, and thus can be further used when assessing subclinical dysfunction in young people with myocardial diseases.